(untitled) (Revista Electrónica Diálogos Educativos. REDE, 2019)
The year 2016 the centenary of the publication of one of the most significant works of the American educator John Dewey Democracy and education (1916) was celebrated with various activities. 2017 commemorated the 100th anniversary of the most significant work of the Chilean educator Dario Salas, El Problema Nacional. Bases para la Reconstrucción de Nuestro Sistema Escolar Primario (1917). In the context of both centenarians the influence of the work of the American educator in the text of the Chilean educator is analyzed.